A study on effectiveness of I-Aslah counter service at Bank Rakyat Likas / Syazwani Sulaiman - Sulaiman, Syazwani (2010)
Islamic banking is growing tremendously since its inception in the past three decades. The products and services offered by the Islamic banking industry either in its assets or liability sides are competitive with the products and services of the conventional banking. The growth of Islamic banking gives alternative to customers in order to choose which alternative bank that serves the best effective service provider. Therefore, the purpose of conducting this study is :